Meaning and Conception of Bioethics and its Realm: Meaning and Conception of Bioethics - Rahbarpour, Mohammad Reza (Bioethics and Health Law Journal (BHL), 2021)
Background and Aim: The present era witnesses new biomedical technologies that have brought about philosophical, moral, religious and social challenges. More questions, challenges and uncertainties in biotechnology have made applied ethics, as a part of its ethics and philosophy, investigate the issue and find relevant appropriate solutions based on ethical principles and theories. Materials and Methods: The current study aimed at casting light on bioethics and its scope using primary and authentic sources on bioethics and seeking the related keywords in these sources. Ethical Considerations: The principles of research ethics have been observed in studies and citing the primary texts and sources. Findings: Providing an all-inclusive definition of bioethics and its place in different disciplines of ethics, this short discussion tackles the area, realm, and significance of the issues in bioethics. Technologies such as assisted reproductive, in vitro fertilization (IVF), human and animal cloning, obtaining stem cells and using them, euthanasia, and manufacture of human organs and their transplantation are the most challenging matters for which within bioethics, the fundamental answers and strategies against the questions and challenges of their emergence are elaborated. Conclusion: Bioethics is a new area of interest in applied normative ethics which, as an interdisciplinary, examines systematically the moral challenges coming from biological science and medical innovations and organizes the must-to-dos in this connection. The realm of bioethics comprises the distinction of consequences of applying modern biomedical technologies against the ethical principles and standards within human life. The aforesaid technologies and advancements that make up issues in bioethics are grouped in four categories: Life preserver technologies at the beginning of life and during it; Life lasting technologies to promote the life quality; Reproductive and esp. cloning technologies; Technologies associated with genetic engineering and gene therapy. *Corresponding Author: Mohammad Reza Rahbarpour; Email: rahbarpour@atu.ac.ir; ORCID: https://orcid.org/0000-0002-2383-6463 Please cite this article as: Rahbarpour MR. Meaning and Conception of Bioethics and its Realm. Bioeth Health Law J. 2021; 1:1-11 (e1). http://doi.org/10.22037/bhl.v1i1.38123